2018
DOI: 10.1186/s12199-018-0741-0
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary monitoring of concentration of particulate matter (PM2.5) in seven townships of Yangon City, Myanmar

Abstract: BackgroundAirborne particulate pollution is more critical in the developing world than in the developed countries in which industrialization and urbanization are rapidly increased. Yangon, a second capital of Myanmar, is a highly congested and densely populated city. Yet, there is limited study which assesses particulate matter (PM2.5) in Yangon currently. Few previous local studies were performed to assess particulate air pollution but most results were concerned PM10 alone using fixed monitoring. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…CPI values close to 1 indicate fossil fuel burning mostly from anthropogenic activities, while values higher than 2 indicate biogenic detritus. July and August 2017 were the only 2 months that had CPI values below 1, suggesting strong biogenic influence rather than anthropogenic sources such as vehicles, as Yi et al [2] proposed in a preliminary PM study in Myanmar. However, there are other sources of alkanes in PM 10 that may also explain this CPI.…”
Section: Source Identification and Mass Reconstructionmentioning
confidence: 81%
See 2 more Smart Citations
“…CPI values close to 1 indicate fossil fuel burning mostly from anthropogenic activities, while values higher than 2 indicate biogenic detritus. July and August 2017 were the only 2 months that had CPI values below 1, suggesting strong biogenic influence rather than anthropogenic sources such as vehicles, as Yi et al [2] proposed in a preliminary PM study in Myanmar. However, there are other sources of alkanes in PM 10 that may also explain this CPI.…”
Section: Source Identification and Mass Reconstructionmentioning
confidence: 81%
“…Although there have not been many emission inventory studies conducted in Yangon, traffic was believed to be the primary source of PM in the city. For example, Yi et al [2] considered traffic as the major source of PM 2.5 in Yangon. Additionally, there was some construction taking place in the city during the sampling period.…”
Section: Study Site and Sampling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two further studies measuring air quality at the ground level in Yangon indicate that outdoor air is highly contaminated with traffic-related pollutants. One of the studies used portable pocket sensors attached to smartphones to measure PM 2.5 in seven townships around Yangon city (Yi et al 2018). They found that concentrations of PM 2.5 in the air exceeded the WHO guidelines, particularly during rush hours due to motor vehicles emissions.…”
Section: Lack Of Budget and Resources For Monitoring Inspection And mentioning
confidence: 99%
“…However, it is important to integrate indoor and outdoor air pollution levels and individual time-activity patterns to generate reliable exposure assessments [13]. Recent studies have used new methodologies to assess exposure for the urban population based on alternative technologies and mobile monitoring approaches [14][15][16]. However, there is still a need to improve the air pollution exposure assessment for a population.…”
Section: Introductionmentioning
confidence: 99%